Characteristics and expression patterns of six α-galactosidases in cucumber (Cucumis sativus L.) - Zhang, Zhi-ping (PLoS One, 2021)
Six putative α-galactosidase genes (α-Gals), three acid forms (CsGAL1, CsGAL2, CsGAL3) and three alkaline forms (CsAGA1, CsAGA2, CsAGAL3), were found in the cucumber genome. It is interesting to know the expression pattern and possible function of these α-Gals in the cucumber plant since it is a stachyose-translocating species. In this study, full-length cDNAs of six α-Gals were cloned and heterologously expressed. The result showed that all recombinant proteins revealed acid or alkaline α-Gal activities with different substrate specificities and pH or temperature responding curves, indicating their distinct roles in cucumber plants. Phylogenetic analysis of collected α-Gal amino acid sequences from different plants indicated that the ancestor of both acid and alkaline α-Gals existed before monocots and dicots separated. Generally, six α-Gal genes are universally expressed in different cucumber organs. CsGAL2 highly expressed in fasting-growing leaves, fruits and germinating seeds; CsGAL3 mainly distributes in vacuoles and significantly expressed in cucumber fruits, senescent leaves and seeds during late stage germination; The expression of CsAGA1 increased from leaf 1 to leaf 3 (sink leaves) and then declined from leaf 4 to leaf 7 (source leaves), and this isoform also highly expressed in male flowers and germinating seeds at early stage; CsAGA2 significantly expressed in cucumber leaves and female flowers; CsAGA3 is localized in plastids and also actively expressed in senescent leaves and germinating seeds; The role of CsGAL1 in cucumber plants is now unclear since its expression was relatively low in all organs. According to their expression patterns, subcellular localizations and previously reported functions of these isoforms in other plants, combining the data of soluble sugars contents in different tissues, the possible functions of these α-Gals were discussed.